Elevated 20-HETE impairs coronary collateral growth in metabolic syndrome via endothelial dysfunction - Joseph, Gregory (Am J Physiol Heart Circ Physiol, 2017)
Coronary collateral growth (CCG) is impaired in metabolic syndrome (MetS). microRNA-145 (miR-145-Adv) delivery to our rat model of MetS (JCR) completely restored and neutrophil depletion significantly improved CCG. We determined whether low endogenous levels of miR-145 in MetS allowed for elevated production of 20-hydroxyeicosatetraenoic acid (20-HETE), which, in turn, resulted in excessive neutrophil accumulation and endothelial dysfunction leading to impaired CCG. Rats underwent 0–9 days of repetitive ischemia (RI). RI-induced cardiac CYP4F (neutrophil-specific 20-HETE synthase) expression and 20-HETE levels were increased (4-fold) in JCR vs. normal rats. miR-145-Adv and 20-HETE antagonists abolished and neutrophil depletion (blocking antibodies) reduced (~60%) RI-induced increases in CYP4F expression and 20-HETE production in JCR rats. Impaired CCG in JCR rats (collateral-dependent blood flow using microspheres) was completely restored by 20-HETE antagonists [collateral-dependent zone (CZ)/normal zone (NZ) flow ratio was 0.76 ± 0.07 in JCR + 20-SOLA, 0.84 ± 0.05 in JCR + 20-HEDGE vs. 0.11 ± 0.02 in JCR vs. 0.84 ± 0.03 in normal rats]. In JCR rats, elevated 20-HETE was associated with excessive expression of endothelial adhesion molecules and neutrophil infiltration, which were reversed by miR-145-Adv. Endothelium-dependent vasodilation of coronary arteries, endothelial nitric oxide synthase (eNOS) Ser1179 phosphorylation, eNOS-dependent NO(·−) production and endothelial cell survival were compromised in JCR rats. These parameters of endothelial dysfunction were completely reversed by 20-HETE antagonism or miR-145-Adv delivery, whereas neutrophil depletion resulted in partial reversal (~70%). We conclude that low miR-145 in MetS allows for increased 20-HETE, mainly from neutrophils, which compromises endothelial cell survival and function leading to impaired CCG. 20-HETE antagonists could provide viable therapy for restoration of CCG in MetS. NEW & NOTEWORTHY Elevated 20-hydroxyeicosatetraenoic acid (20-HETE) impairs coronary collateral growth (CCG) in metabolic syndrome by eliciting endothelial dysfunction and apoptosis via excessive neutrophil infiltration. 20-HETE antagonists completely restore coronary collateral growth in metabolic syndrome. microRNA-145 (miR-145) is an upstream regulator of 20-HETE production in metabolic syndrome; low expression of miR-145 in metabolic syndrome promotes elevated production of 20-HETE.